ANALISIS RISIKO SAHAM PERUSAHAAN FINANCE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Theodora Novalina Ariesta; Khaira Amalia Fachrudin (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT This research is aimed to determine and analyze the differences of systematic risk and unsystematic risk in Bank subsector, Finance subsector, Securities Company subsector, Insurance subsector, and Others subsector of the finance sector in Indonesian Stock Exchange. Data collection was performed by collecting secondary data from annual financial reports of finance sector consisting of the daily stock price from January 1 until December 31, 2012. The analyze method that is done using One Way ANOVA Test and then Correlation Test from the subsector which have difference unsystematic risk. The sample of this research is 65 finance companies. The result of One Way ANOVA Test shows that from the α 5%, there is no difference of systematic risk between the Bank subsector, Finance subsector, Securities Company subsector, Insurance subsector, and Others subsector of the finance sector in Indonesian Stock Exchange. The result of One Way ANOVA Test also shows that there is difference of unsystematic risk between the Bank subsector, Finance subsector, Securities Company subsector, Insurance subsector, and Others subsector of the finance sector in Indonesian Stock Exchange. The difference is then seen with Correlation Test and the result shows that the unsystematic risk relation of Finance and Others is positive and not significant, unsystematic risk relation of Insurance and Others is positive and not significant, unsystematic risk relation of Bank and Others is negative and not significant, unsystematic risk relation of Securities Company and Others is negative and not significant.